Dynamic linkages among SAMI Nations (Saudi Arabia, Turkey, Malaysia, Indonesia) equity markets - Youcef, Grimes; Adewale, Abideen Adeyemi (IIUM Press, International Islamic University Malaysia, 2017)
This research paper investigates the dynamic linkages among four selected equity markets from Organization of the Islamic Conference (OIC) members. The four countries comprised the proposed Muslim BRICS called SAMI: Saudi Arabia, Ankara (Turkey), Malaysia and Indonesia. The study explores the short and long run linkages between these stock markets for the period spanning from January 2000 to September 2014 split into two sub-periods before and after the global financial crisis. Through applying Johansen co-integration analysis we found that the Indonesian, Malaysian, Saudi Arabian and Turkish stock markets are co-integrated during both periods. Emphasis was on the after crisis period where two co-integrating equations have been recorded. Granger causality test employed based on VECM further revealed that only a unidirectional relationship exist in the pre-crisis period between Saudi Arabia and Indonesia. However, bidirectional causality relationships were detected between almost all the four stock markets during the post-crisis period.